Enhancing Youth Agricultural Literacy with Vertical Farming in Non-Formal Education Settings - Damayanti, Adhisty Puri; Norbertus Citra Irawan; Natalia Deswita Fitriyani; Zainal Mustofa; Agustina Tri Suryaningsih; Dewi Rahmawati Intan Permatasari (Universitas Tunas Pembangunan Surakarta, 2025)
Urban youth often lack access to practical agricultural education, especially in non-formal learning environments where structured curricula are limited. The community faces increasing challenges in food security, environmental awareness, and sustainable skill-building among students with limited exposure to farming. The community service program aimed to improve students’ understanding of vertical agriculture through practical and inclusive educational activities. The facilitators delivered hands-on workshops at PKBM Cahaya Rejeki, involving 20 students in interactive sessions using recycled materials to build vertical gardens in limited urban spaces. The team applied the Wilcoxon Matched-Pairs Signed-Rank Test to compare students’ pre-test and post-test results, finding a statistically significant increase in their agricultural knowledge. Field observations confirmed the positive outcome, as students showed increased enthusiasm, curiosity, and confidence throughout the activities. The program bridged educational and environmental gaps by offering a simple, relatable, and replicable gardening model. The initiative demonstrated that vertical gardening could serve as a powerful tool to promote sustainability, practical skills, and ecological literacy among underserved urban youth. The findings suggest that local governments, educators, and community institutions should collaborate to integrate urban farming into non-formal education programs, thereby ensuring a broader impact and promoting long-term behavioral change.